THE PREVALENCE OF TEMPOROMANDIBULAR DISORDERS AMONG ORTHODONTIC PATIENTS IN KSA (CAHIERS MAGELLANES-NS, 2024)
Background: This article discusses the prevalence of temporomandibular disorder among orthodontic patients in Saudi Arabia. It covers topics like the relationship between TMD and orthodontic treatment and the symptoms and severity of TMD.TMD is a wide variety of conditions affecting the temporomandibular joints and facial muscles and their associated structure.Objective: The main objective of this study was to determine the prevalence of temporomandibular disorder among orthodontic patients in Saudi Arabia.Methods: This study is a cross-sectional questionnaire survey in Saudi Arabia. The cross-sectional questionnaire was carried out between July to November 2024. The study recruits’ participants through social media platforms like Twitter, Snapchat, Instagram, WhatsApp, and Facebook. The inclusion criteria for this study were as follows: any patient who had or has orthodontic treatment in both genders at any age of Saudi populations, and any patient who has not done orthodontic treatment were excluded from this study. The minimum target sample size of 384 was calculated using a formula based on prevalence estimation, 95% confidence level, and 5% acceptable error.Results: Regarding the prevalence of temporomandibular disorders among orthodontic patients, our findings indicated that 80% of participants had undergone orthodontic treatment, primarily using traditional metal braces (72%). Notably, 40.6% reported experiencing pain prior to treatment. While the majority did not report significant difficulties with mouth movement, 31% experienced muscular fatigue and pain while chewing, and 31.1% reported occasional headaches, highlighting common discomforts linked to TMD. Furthermore, 57.1% described themselves as “nervous,” suggesting possible psychological influences on TMD symptoms. Oral habits like teeth clenching and grinding were noted by 41.1% of participants, indicating their potential exacerbation of TMD issues. Statistical analysis revealed significant associations between TMJ pain and factors like gender and age, while other sociodemographic characteristics, such as residential region and income, showed no significant correlation. Conclusion: The study highlighted the high prevalence of TMD among orthodontic patients in Saudi Arabia, finding that most of participants had been treated for orthodontics based mainly on obsolete metal braces. Although there is unanimity among most orthodontists that TMD cannot be made worse by orthodontic intervention, a large portion of participants experienced discomfort related to TMD, including muscular fatigue and headaches.